Pemaknaan Afiks Ter- dalam entuk Polimorfemis (?) - ary Setyadi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2020)
The ability to combine affixes with other morphemes in the form of polymorphism is interesting to study, because the ability to join with other factors influences the determination of various meanings. The determination of the meaning of an affixed lingual unit must start from the (existing) form and then to the meaning.The study of the form of affixes polymorphic morphemes is based on the application of linguistic theory in the field of morphology, because the data problem is related to the complex morpheme shape. Sources of data depart, both from oral data sources and written data sources, so that existing data are primary and secondary.The results of the data analysis show that the initial data is not data that is directly used as a basis for determining, but must first consider the sentence structure pattern (for the sake of structuring the logic elements and structuring grammatical elements).Keywords: Affixes; shape; morpheme; polymorphism. IntisariKemampuan daya gabung afiks ter- dengan morfem lain dalam bentuk polimorfemis menarik dikaji, sebab dari kemampuan bergabung dengan morfem lain berpengaruh atas penentuan bermacam makna. Penentuan makna satu satuan lingual berunsur afiks ter- harus bermula dari bentuk (yang ada) baru kemudian ke makna.Pengkajian bentuk morfem polimorfemis berunsur afiks ter- bertolak pada penerapan teori linguistik bidang morfologi, sebab persoalan data berkait dengan bentuk morfem kompleks. Sumber data bertolak, baik dari sumber data lisan maupun sumber data tulis, sehingga data yang ada bersifat primer dan sekunder.Hasil analisis data menampakkan bahwa data awal bukan merupakan data yang secara langsung dipakai sebagai bahan pijakan penentuan maka, tetapi harus terlebih dahulu perlu diperhatikan pola struktur kalimatnya (demi kebenaran penataan unsur logika dan penataan unsur tata bahasa).Kata kunci; Afiks; bentuk; morfem; polimorfemis.